Cross-border business development in the Dutch-German borderland - Pijnenburg, Vincent; Szillat, Patrick; Lucas, Jan (Shaker, 2021)
Inhaltsverzeichnis: https://d-nb.info/1236587456/04
Keywords: Grenzüberschreitende Kooperation; Wirtschaftsbeziehungen; Wirtschaftsentwicklung

The economic impact of cross-border work on the municipalities of residence. An example at the French–Luxembourgish border - Pigeron-Piroth, Isabelle; Belkacem, Rachid (Border experiences in Europe: everyday life - working life - communication - languages, 2020)
Keywords: Grenzarbeitnehmer; Wirtschaftsentwicklung

The Bottom-Up Approach. Experiences with the Impact Assessment of EU and National Legislation in the German, Dutch and Belgian Cross-Border Regions - Unfried, Martin; Kortese, Lavinia Susan Josephine; Bollen-Vandenboorn, Anouk (Territorial Impact Assessment, 2020)
Aus den Verlagsangaben: „Considering the myriad cross-border regions that the EU counts, it is impossible for the European Commission to map detailed territorial cross-border effects in all of the EU’s border regions for the impact assessments it conducts. National governments also face obstacles when seeking to cohesively integrate cross-border impact assessments in the existing frameworks that they use to assess the impact of new legislative, policy and enforcement measures. Even border regions or cross-border entities themselves face challenges in implementing impact assessments in their own territories. Despite the need for structural analyses of the border effects of newly adopted legislation and legislation under review, in terms of policy and enforcement, there are issues regarding the availability of academic resources, relevant tools and know-how. For the last couple of years, researchers from Maastricht University have been assessing as a bottom up exercise the potential effects of legislative proposals on the specific Dutch/German and Dutch/Belgium cross-border territories. This article presents the methodology used and the experiences gained from 2016 to 2019 by highlighting a number of interesting cases. It also offers future ideas for conducting similar “bottom-up” regulatory territorial impact assessments in cross-border regions.“
Keywords: Euregio Maas-Rhein; Gesetzgebung; Grenzgebiet; Wirtschaftsbeziehungen; Wirtschaftsentwicklung

Ein grenzüberschreitender Wirtschaftsraum? Gemeinsame und individuelle Entwicklungen seit der Krise des Montansektors - Dörrenbächer, H. Peter (Lebenswirklichkeiten und politische Konstruktionen in Grenzregionen. Das Beispiel der Großregion SaaLorLux. Wirtschaft – Politik – Alltag – Kultur, 2015)
Abstract: „Dieser Beitrag beschreibt und analysiert den Strukturwandel im SaarLorLux-Raum und geht dabei der Frage nach, ob dieser noch eine gemeinsame Wirtschaftsregion darstellt. Das Saarland, Lothringen und Luxemburg bildeten lange Zeit einen gemeinsamen Wirtschaftsraum, der vom Montansektor geprägt wurde. Seit Anfang der 1960er-Jahre erlebten alle drei Regionen – zunächst im Zuge der Kohlenkrise, später der Stahlkrise – einen tiefgreifenden Strukturwandel. Dieser Wandel verlief in den einzelnen Regionen recht unterschiedlich: Im Saarland und in Lothringen wurden viele Industriebetriebe angesiedelt; heute bildet die Automobilindustrie einen wesentlichen Schwerpunkt in beiden Regionen. In Luxemburg dagegen entwickelten sich der Dienstleistungssektor und insbesondere der Finanzsektor außerordentlich dynamisch. In der Europäischen Union hat Luxemburg heute das höchste Bruttoinlandsprodukt, sodass hinterfragt werden kann, ob das Saarland, Lothringen und Luxemburg noch eine gemeinsame Wirtschaftsregion bilden. Trotz der unterschiedlichen Entwicklung in den drei Regionen kann am Konzept der grenzüberschreitenden Wirtschaftsregion SaarLorLux festgehalten werden, wenngleich dieses keine identische Wirtschaftsstruktur und -entwicklung in den Teilgebieten unterstellt. Die Wirtschaftsregion SaarLorLux ist vielmehr von Heterogenitäten und darauf basierenden Austauschprozessen gekennzeichnet.“
Keywords: Eisen- und Stahlindustrie; Steinkohlenbergbau; Strukturwandel; Wirtschaftsbeziehungen; Wirtschaftsentwicklung

The development of cross-border economic relations. A theoretical and empirical study of the influence of the state border on the development of crossborder economic relations between firms in border regions of the Netherlands and Belgium - Houtum, Henk van (1998)
Zugl.: Tilburg, Katholieke Univ. Brabant, Diss., 1998
Keywords: Wirtschaftsentwicklung